Jaw-jaw and war-war. (Economist, 2018)
The article focuses on the development of a new type of battlefield network that is expected to improve military communications. It discusses how a mobile ad hoc network (MANET) can avoid the pre-programming required by existing systems. The role of the U.S. Defense Advanced Research Projects Agency (DARPA) in the development of the MANET is also explored.